Americas remixed. - Arratia, Euridice; Brandirali, Aldo; Budney, Jen; Pinto, Roberto; Sirmans, Franklin; Comune di Milano; Artshow Edizioni, Milano (Cinisello Balsamo, Milano : Silvana Editoriale, 2002)
Baran, Tracey ; Binion, McArthur ; Blondeau, Lori ; Brown, Iona ; Chang, Patty ; Cordova, William ; Diamond, Stephanie ; Ei-chi Deforest, Kevin ; Eshkar, Shelley ; Kaiser, Paul ; Gatson, Rico ; Gutierrez, diego ; Jones, Jennie c. ; Lemieux, Corine ; Lennon, Jno Baptiste ; McKenzie, Dave ; Moody, Robyn ; Opdyke, David ; Partegas, Ester ; Rammellzee ; Spang, Bently ; Thomas, Jeff
ind. tent., gr. tent. per kunstenaar p. 40-120
Italiaans & Engels
Americas remixed, Fabbrica del Vapore Milano, Comune di Milano, 24.9. - 27.10.2002
boek